Lingkup Dan Jaringan Kerjasama Di Dunia Cyber - Lubis, Suci Arifah; Harahap, Adrie Fachrezi; Nurbaiti, Nurbaiti (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Technology can be said to be a gift but if cn also be said to be a thret to its users. For ecample the virtul world and the internet, cyberspace or the internet can connect millions of peopple in variouse communications from various places. The internet is certainly very flower among people and the internet has also been recognized as very useful and supports almost every area of lifeIndonesia makes ASEAN countries to implement the proposals. Cybercrime is a matter of widespread concern in ASEAN. ASEAN is an association that works for the monetary progress of countries in Southeast Asia. These countries consist of Myanmar, Thailand, Laos, Cambodia, Vietnam, Malaysia, Singapore, Indonesia, Brunei, and the Philippines. In 2015, the ASEAN Community was established in three columns joining the ASEAN states. The main column is the ASEAN Political and Security Community, the next column is the ASEAN Economic Community, and the third column is the ASEAN Social and Cultural Community.